Finite State Machine untuk Menghasilkan Kalimat Sebagai Alat Bantu Komunikasi Bagi Anak Penyandang Autisme - Steven Hans Gunadi Chua; Liliana Liliana; Lily Eka Sari (Jurnal Infra, 2021)
One of the obstacles for children with autism is communication. Children with autism, who are nonverbal, have difficulty interacting with other people or just expressing their needs. When the child's wishes are not fulfilled, the child with autism will tend to throw a tantrum, which may be harmful because it can hurt the child. Currently, there is intervention by using the PECS method that can help children with autism learn to communicate by using picture cards. However, the drawback of this PECS method is the large number of picture cards that must be provided for children with autism.In this study, an Android application was created as a communication tools to children with autism learn to communicate. The application follows the stages of using PECS and also utilizes the finite state machine to generate sentences.Based on the results of this study, the application was able to help children with autism, who are nonverbal to communicate, although some children need more time to understand how to use the application.